PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA - Dikson Pardamean Aritonang; Wawan Prahiawan (Universitas Bina Taruna Gorontalo, 2024)
This research aims to explore the influence of career development on job satisfaction through a qualitative approach. Job satisfaction is one of the variables for companies to achieve good employee productivity results for the company. The study examines how the relationship of career development affects employees' perceptions of their job satisfaction. Drawing from previous research and through descriptive analysis, it is concluded that career development has a significant influence on job satisfaction. These findings provide a deep understanding of the relationship between career development and job satisfaction within organizations. The implications of this research can assist organizations in designing more effective career development programs and management policies that support employee well-being and enhance overall organizational performance.